Who? What? Where? A snapshot of Nuclear Medicine Research Presentations from recent ANZSNM conferences in Australia and New Zealand. - Jo-Anne Pinson (Asia Oceania Journal of Nuclear Medicine and Biology, 2020)
Objective(s): The aims of this study were to: 1) discover location (by city) of contributors to poster and oral presentations at recent ANZSNM conferences; 2) determine the nuclear medicine themes most commonly explored; 3) establish institutions producing the highest number of oral and poster abstracts and 4) determine publication rates of conference abstracts to full papers from recent ANZSNM conferences. Methods: Retrospective analysis of abstracts published in the Internal Medicine Journal Special Issues 2014–2019 identified 614 abstracts. Invited plenary speaker abstracts were excluded. Descriptive statistics were used in data analysis. Conference abstracts were analysed using the following criteria: poster or oral presentation, author/s, city location, hospital and subject matter. Themes defined by the ANZSNM conference committee for abstract submission were: cardiology, oncology, neurology, therapy, renal/urology, gastrointestinal, paediatrics, musculoskeletal, infection/inflammation, technology, physics, radiation safety, radiopharmacy/radiochemistry, education, or general. Retrospective analysis of 555 conference abstracts (excluding New Zealand and International, 59 abstracts) using Google Scholar, Pubmed and Google databases was undertaken. Abstract titles, key words, institutions and/or authors’ names were used to find peer-reviewed papers. Identified papers were authenticated through either open access, publicly available author information or Monash University’s library access. Published paper citations were also recorded (up to 1st July 2019). Results: Analysis of 614 abstracts 2014 – 2019 was performed. Over five years, the average number of poster abstracts was 67.8 and oral 55.0. Sydney submitted the highest number of poster abstracts, while Melbourne the highest number of oral abstracts. Most popular abstract theme was oncology for both poster and oral abstracts. Publications found had in excess of 1250 citations.One hundred and one publications from one hundred and seven conference presentations were identified, distributed across sixty journals. Conference presentation to full publication rate was 18.2%; excluding 2019 conference abstracts the rate was 21.5%. Conclusion: Publishing research findings is a challenging process. A retrospective analysis of research presented at recent ANZSNM conferences by abstract content was undertaken, with conference presentation to full publication rate found to be at the lower end of reported literature findings.